Laboratory diagnosis of sexually transmitted infections in estonia in 2001-2002: shortcomings with impact on diagnostic quality and surveillance - Naaber, Paul; Uusküla, Anneli; Naaber, Janika; Põder, Airi; Hjelm, Eva; Hallén, Anders; Unemo, Magnus; Domeika, Marius (Sexually transmitted diseases, 2005)
The objectives of this study were to comprehensively characterize the range, content, and performance of sexually transmitted infection (STI) testing services in Estonia during the period 2001 to 2002 and to determine if the observed diagnostic laboratory practices and methods adhered to international evidence-based recommendations. Survey data, focusing on organization and performance characteristics of STI diagnostics services, were assessed using questionnaires, telephone interviews, and site visits to all responding facilities providing STI diagnostics services in Estonia. Guidelines of international evidence-based recommendations for STI testing were used as references. There were significant shortcomings in STI testing availability and practices. Among all participating laboratories diagnosing STIs, only a minority (n = 16, 28%) offered testing for the full minimum range of relevant STIs in Estonia, i.e., Treponema pallidum, Neisseria gonorrhoeae, Chlamydia trachomatis, and Trichomonas vaginalis. In addition, because testing methods used were not properly selected, confirmation of several infections in accordance with evidence-based requirements was not possible, which has an impact both on STI diagnostic quality and surveillance.